Physiotherapy-as-first-point-of-contact-service for patients with musculoskeletal complaints: understanding the challenges of implementation. Issue 2 (12th September 2017) - Moffatt, Fiona; Goodwin, Rob; Hendrick, Paul
Abstract : Background: Primary care faces unprecedented challenges. A move towards a more comprehensive, multi-disciplinary service delivery model has been proposed as a means with which to secure more sustainable services for the future. One seemingly promising response has been the implementation of physiotherapy self-referral schemes, however there is a significant gap in the literature regarding implementation. Aim: This evaluation aimed to explore how the professionals and practice staff involved in the delivery of an in-practice physiotherapy self-referral scheme understood the service, with a focus on perceptions of value, barriers and impact. Design and setting: A qualitative evaluation was conducted across two UK city centre practices that had elected to participate in a pilot self-referral scheme offering 'physiotherapy-as-a-first-point-of-contact' for patients presenting with a musculoskeletal complaint. Methods: Individual and focus group interviews were conducted amongst participating physiotherapists, administration/reception staff, general practitioners (GPs) and one practice nurse (in their capacity as practice partner). Interview data were collected from a total of 14 individuals. Data were analysed using thematic analysis. Results: Three key themes were highlighted by this evaluation. First, the imperative of effecting a cultural change – including management of patient expectation with particular reference to the belief that GPs represented the 'legitimate choice', re-visioning contemporary primary care as a genuine team approach, and the physiotherapists' reconceptualisation of their role and practices. Second, the impact of the service on working practice across all stakeholders – specifically re-distribution of work to 'unburden' the GP, and the critical role of administration staff. Finally, beliefs regarding the nature and benefits of physiotherapeutic musculoskeletal expertise – fears regarding physiotherapists' ability to work autonomously or identify 'red flags' were unfounded. Conclusion: This qualitative evaluation draws on the themes to propose five key lessons which may be significant in predicting the success of implementing physiotherapy self-referral schemes.